2016
DOI: 10.1007/s13277-016-5322-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic distribution of single nucleotide polymorphisms in oral cancer: global scene

Abstract: Globocan 2012 reports the global oral cancer incidence of 300,373 new oral cancer cases annually, contributing to 2.1 % of the world cancer burden. The major well-established risk factors for oral cancer include tobacco, betel/areca nut, alcohol and high-risk oncogenic human papilloma virus (HPV) 16/18. However, only 5-10 % of individuals with high-risk lifestyle develop oral cancer. Thus, genomic variants in individuals represented as single nucleotide polymorphisms (SNPs) influence susceptibility to oral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Approximately 20–30% breast cancers show 40–100 fold elevated levels of Her2 , whereas other cancer types such as ovarian, endometrial, gastric and esophageal cancers were also detected with over-expressed Her2 protein levels 65 71 . Single nucleotide polymorphisms (SNPs) are playing an important role in various cancer types and are capable of serving as diagnostic tools 23 25 . One such single nucleotide polymorphism with substitution of isoleucine with valine at codon 655 in transmembrane region of Her2 has been found to be playing an important role in development of cancer 72 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20–30% breast cancers show 40–100 fold elevated levels of Her2 , whereas other cancer types such as ovarian, endometrial, gastric and esophageal cancers were also detected with over-expressed Her2 protein levels 65 71 . Single nucleotide polymorphisms (SNPs) are playing an important role in various cancer types and are capable of serving as diagnostic tools 23 25 . One such single nucleotide polymorphism with substitution of isoleucine with valine at codon 655 in transmembrane region of Her2 has been found to be playing an important role in development of cancer 72 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic epidemiological studies indicated association between single nucleotide polymorphisms and different cancers 23 25 . Cell cycle regulatory role of Her2 and its importance in prognosis of breast cancer clearly indicates that polymorphism in coding region of Her2 might be associated with either cancer susceptibility risk or resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have provided evidence regarding aberrant expression of tumorigenic genes in OSCC and cancer diagnostic and prognostic biomarkers. Single nucleotide polymorphisms in the coding and noncoding RNA genes have been analyzed most commonly [27][28][29]. This study is the first, to our knowledge, to investigate the role of X-linked genes in saliva in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation is seen in Asian countries with less than 15% mortality due to tobacco in oral cancer . An inherent role of the genomic constitution is considered as a predisposition or protective factor in oral carcinogenesis . The complex multifactorial molecular landscape of oral cancer encompasses somatic mutations, deregulated expression, epigenetic regulation via DNA methylation, histone modification, and microRNAs, and genomic variants …”
Section: Introductionmentioning
confidence: 99%